PENGARUH MODEL PBL TERHADAP KETERAMPILAN BERPIKIR TINGKAT TINGGI MATERI PENCEMARAN LINGKUNGAN KELAS VII SMP - Wahyuni, Titik Widya; Ningsih, Kurnia; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to identifying the effect of Promblem Based Learning model to the Higher Order Thinking Skills students on environmental pollution subject at seventh grade of SMP Negeri 1 Sungai Raya. This research form was quasy experimental design with nonequivalent control group design. The sampling technique used was intac group, with VII C as the experimental class and VII A as the control class. The instrument was 10 questions of essay test. The average score of Higher Order Thinking Skills test of the experimental class was 42 and the control class was 33.50 with a maximal score of 56. Based on U Mann-Whitney test results, obtain Zcount (-4.75) < -Ztabel (-1.96), that means there was a significant differences between the Higher Order Thinking Skills using Problem Based Learning model and conventional model. The value of effect size obtained in this research was 1.53 which could be classified as high category and has an effect as much as 43.70%.Â Keyword : Environmental Pollution Subject, Higher Order Thinking Skills, Problem Based Learning